A new Cretaceous terrestrial ecosystem from Gondwana with the description of a new sauropod dinosaur - Jorge O. Calvo (Anais da Academia Brasileira de Ciências, 2007)
A unique site at the northern area of Patagonia (Neuquén, Argentina) reveals a terrestrial ecosystem preserved in adetail never reported before in a Late Cretaceous deposit. An extraordinary diversity and abundance of fossils wasfound concentrated in a 0.5 m horizon in the same quarry, including a new titanosaur sauropod, Futalognkosaurus dukein.gen., n.sp, which is the most complete giant dinosaur known so far. Several plant leaves, showing a predominance ofangiosperms over gymnosperms that likely constituted the diet of F. dukei were found too. Other dinosaurs (sauropods,theropods, ornithopods), crocodylomorphs, pterosaurs, and fishes were also discovered, allowing a partial reconstructionof this Gondwanan continental ecosystem.